Raman signatures of strong and weak hydrogen bonds in binary mixtures of phenol with acetonitrile, benzene and orthodichlorobenzene. (24th January 2016) - Singh, Anurag; Gangopadhyay, Debraj; Nandi, Rajib; Sharma, Poornima; Singh, Ranjan K.
Abstract : The present study aims at investigating the effect of hydrogen bonds of phenol in binary mixtures of phenol with three solvents viz. acetonitrile, orthodichlorobenzene and benzene respectively in order of decreasing hydrogen bond strength. Raman spectroscopy in correlation with density functional theory (DFT) calculations has led to a profound understanding of changes in structure, energy, dipole moment and other physical and chemical properties of phenol pertaining to hydrogen bond formation in solution. The spectral variation in wavenumber and linewidth of ring deformation, ring stretching, C≡N stretching and C―H stretching modes have been analyzed in detail. The breaking of self association of phenol in solution and formation of strong or weak hydrogen bonds depending on the nature of the solvent has been discussed by comparing the Raman and DFT results for three different solvents. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Raman spectroscopy in correlation with density functional theory calculations has led to a profound understanding of changes in structure, energy, dipole moment, and other physical and chemical properties of phenol pertaining to hydrogen bond formation in binary mixtures with acetonitrile, benzene, and orthodichlorobenzene. The breaking of self‐association of phenol in solution and formation of strong or weak hydrogen bonds depending on the nature of the solvent is evident from the Raman spectral data.